Implementation Of the IQRA' Method to Improve The Quran Reading Quality Of The Students of Harfan Maftahil Bilad Boarding School - Rizkasetyo Hidayah (LP2M UIN KH.Achmad Siddiq Jember, 2023)
Learning the Qur'an is currently progressing along with the times and technology. Various methods of teaching the Qur'an are used by Ustaz and Ustadz in various Islamic boarding schools in Indonesia. Due to the many problems faced and technological advances, children need to learn the Qur'an from an early age to form morals from an early age. Therefore, it is important for children to learn to read from an early age, especially the Qur'an, especially using recitation techniques to facilitate the achievement of the objectives of learning the Qur'an correctly. In this study, one of the reading methods, namely the iqra method, was used to improve the quality of reading the Qur'an by the students of the Harfan Mafatihil Bilad Islamic Boarding School. The method used in this research is a qualitative approach. The target of this research service is the students of the Harfan Mafatihil Bilad Islamic Boarding School, West Tegalbadeng Village.